Broad spectrum weed control in wheat with pyroxsulam and its tank mix combination with sulfosulfuron - Chhokar, Rajender Singh; Sharma, Ramesh Kumar; Gill, Subhash Chander; Singh, Ram Kumar (Journal of Cereal Research, 2019)
Field and pot studies were conducted to determine the efficacy of pyroxsulam and tank mix combination of sulfosulfuron + pyroxsulam against diverse weed flora of wheat (Triticum aestivum L.). In field studies, pyroxsulam (12, 15 and 18 gha-1 ) and tank mix combination of sulfosulfuron + pyroxsulam at 12+12, 15+15 and 18+18 gha-1 without and with surfactant were evaluated for weed control in wheat and their carry over effect on succeeding sorghum crop. The weed control, particularly of the Phalaris minor was significantly poor, when pyroxsulam or its tank mix combination with sulfosulfuron were applied without surfactant compared to with surfactant (polyglycol 1000 ml ha-1). Pyroxsulam alone or in combination with sulfosulfuron provided excellent control of Avena ludoviciana. The optimum dose of tank mixture (TM) of sulfosulfuron + pyroxsulam was 18+18 gha-1 with 1000 ml ha-1 surfactant polyglycol. This combination was superior over sulfosulfuron, due to improved control of Rumex dentatus, therebyincreased the wheat yield by 10-11% (on three years mean basis).Â The TM, sulfosulfuron + pyroxsulam with surfactant was similar to ready mixture Atlantis (mesosulfuron + iodosulfuron) at 14.4 (12+ 2.4) g a.i. ha-1 in controlling weeds and producing wheat yield. Pyroxsulam at 18 gha-1 was effective for control of diverse weed flora (Avena ludoviciana, Phalaris minor, Medicago denticulata and Lathyrus aphaca) under field and pot studies. The carry over effect of sulfosulfuron involving treatments (sulfosulfuron, sulfosulfuron + pyroxsulam) was observed on succeeding sorghum crop. At 18+18 gha-1 dose of sulfosulfuron + pyroxsulam, the average reduction in sorghum biomass was 44.5% in comparison to no herbicide treatment. Pyroxsulam effectively controlled the P. minor populations being susceptible as well as those resistant to fop and / or phenylurea herbicides. However, P. minor population resistant to sulfosulfuron showed the cross-resistance to pyroxsulam.